(untitled) (Glocal Society Journal, 2024)
The Rohingya Crisis in 2017 has called for widespread condemnation of Myanmar. However, reports on this event have only escalated tensions. This paper explores the practice of peace/war journalism by an international media, Aljazeera, in reporting such a crisis. To do so, this research utilizes Lynch’s peace journalism framework as a standard of conflict-sensitive media. This paper argues that evidence of peace journalism does exist, but other factors imply that war journalism is still strong. Such practice of war journalism has (1) disregarded the crisis’ global ramifications; (2) put a narrow context that ignores Myanmar’s democratic struggle; (3) portrays conflicting parties’ religious relationships as victim-perpetrators; (4) dehumanized Buddhists, monks, and the Myanmar people in general; (5) lacked accounts from grassroots peacemakers; and (6) created an excessive emphasis on elite-level negotiation, particularly in light of pressure from world leaders.